Unveiling the BIM Execution Plan (BEP): a comprehensive review of global frameworks and applications - Mat Sahizol Raduan, Syahirah; Brahim, Juliana; Mohd Nordin, Rumaizah; Mohd, Suzila; Fajarianto, Otto (UiTM Press, 2025)
Building Information Modelling (BIM) has significantly transformed the construction industry by enhancing project efficiency and collaboration throughout the project lifecycle. The BIM Execution Plan (BEP) serves as a critical framework to guide construction professionals in implementing BIM effectively. However, while the BEP is intended to provide a comprehensive guideline for BIM-based construction projects, many stakeholders failed to fully leverage its benefits, often reducing it to a mere template or formality initiated at the start of a project. This study aims to review existing research related to BEP frameworks within the construction industry to guide successful BIM implementation. The findings reveal that while existing BEP frameworks outline essential elements such as project information, BIM deliverables, workflows, and quality control, only a limited number of studies provide practical guidance on their full utilisation in real-world construction projects. Furthermore, challenges such as inconsistent BEP content, lack of actionable strategies, and limited stakeholder engagement hinder its adoption and integration. This research is expected could highlight the need for a more structured and practical approach to BEP implementation, particularly in developing countries such as Malaysia, where existing frameworks remain underutilised. Hence, this research is significant for the Malaysian construction industry as it aims to bridge the gap between BEP theory and practice, enabling professionals to maximise the benefits of BIM and achieve better project outcomes.